ESTIMATING SENSIBLE HEAT LOSS IN CONFINED LAMB UNDER COLD STRESS - HOSTALÁCIO, Afonso N.; MATOS, Márcia C.; SOUZA, Márcio R.; CENTURION, Ruben Alejandro OVELAR; NÄÄS, Irenilza de A. (Revista Brasileira de Engenharia de Biossistemas, 2010)
This study aimed to estimate the loss of sensible heat in feedlot of lambs and to quantify the metabolic energy to maintain body temperature under cold stress. Twenty four crossbred lambs (mean 120 days of age, 26.3 kg of body weight and on diet with 2.94 kcal animal-1 day of metabolic energy). Six animals were randomly selected and used like reference to the rearing environmental parameters: minimum and maximum air temperature, air velocity, relative humidity and lighting. To estimate the average energy expenditure surface temperatures in the regions of head, ears and legs were considered, using the infrared thermal images and corresponding software. During the period the temperature was below the thermal comfort zone, and that the lambs' average body surface temperature was 11.48 ± 0.92° C, indicating that there was an interaction between climatic parameters evaluated which promoted cooling of the environment and influenced the reduction of the animals' surface temperature. The total dissipation of sensible heat in the animals' analyzed parts was 39.18 W, which corresponds to the consumption of 0.388 kcal 12 h-1. It was found that 26.4% of daily metabolic energy intake by the lambs in the days of temperature below the thermal comfort zone was used for thermogenesis. However, it was verified the animals were housed below the zone of thermal comfort, and that the sensible heat dissipated by convection and radiation, using part of metabolic energy to maintain body temperature, which might lead to economic losses of production.